Liver resection for atypical giant focal nodular hyperplasia - Dmitry Akhaladze; Nikolay Grachev; Denis Kachanov; Sergey Talypov; Nikolay Merkulov; Natalia Uskova; Evgeniy Andreev; Gavriil Rabaev; Natalia Ivanova; Svetlana Varfolomeeva (Elsevier, 2019)
Focal nodular hyperplasia (FNH) usually presents in children with underlying liver disease, in patients undergone chemotherapy and adolescent females. The reports, describing huge FNH with severe dilatation of the right hepatic vein (RHV) in healthy children are absent.A 2,7 years old boy without any comorbidities was presented with intermittent abdominal pain and a huge mass, causing the abdominal asymmetry. The initial imaging showed the giant mass (more than 125 mm in the biggest dimensions), with sings of the atypical FNH It was arising from 5,6 liver segments, and was accompanied with strong expansion of the RHV. According to CT-volumetry, the lesion volume exceeded the right hepatic lobe volume on 350 ml. Despite the all signs of atypical FNH and absence of underlying liver diseases, the surgery without preoperative biopsy was carried out. Postoperative course was uneventful. The pathological examination confirmed the diagnosis - focal nodular hyperplasia of the liver. The postoperative computed tomography showed the RHV, returned to its physiological size.Giant atypical FNH may occur in very young children. Huge size of the tumor can lead to severe dilatation of the RHV, which can be reversible. The surgical resection is the treatment of choice in such cases. Keywords: Huge focal nodular hyperplasia, Children, Liver resection, Hepatic vein dilatation